Effect of Variable Thermal Conductivity on the Generalized Thermoelasticity Problems in a Fiber-Reinforced Anisotropic Half-Space - Chun-Bao Xiong; Li-Na Yu; Yan-Bo Niu (Advances in Materials Science and Engineering)
Fiber-reinforced materials have widespread applications, which prompt the study of the effect of fiber reinforcement. Research studies have indicated that thermal conductivity cannot be considered as a constant, which is closely related to temperature change. Based on those studies, we investigate the fiber-reinforced generalized thermoelasticity problem under thermal stress, with the consideration of the effect of temperature-dependent variable thermal conductivity. The problem is assessed according to the L-S theory. A fiber-reinforced anisotropic half-space is selected as the research model, and a region of its surface is subjected to a transient thermal shock. The time-domain finite element method is applied to analyze the nonlinear problem and derives the governing equations. The nondimensional displacement, stress, and temperature of the material are obtained and illustrated graphically. The numerical results reveal that the variable conductivity significantly influences the distribution of the field quantities under the fiber-reinforced effect. And also, the boundary point of thermal shock is the most affected. The obtained results in this paper can be applied to design the fiber-reinforced anisotropic composites under thermal load to satisfy some particular engineering requirements.